SPECIFICS OF ACTIVE ORThOSTATIC TEST IN PATIENTS WITH CHRONIC HEART FAILURE - V. A. Kuznetsov; P. V. Shebeko; T. N. Enina; N. N. Melnikov; T. I. Petelina; A. M. Soldatova (Российский кардиологический журнал)
Aim. To reveal clinical and morphofunctional and biochemical differences among patients with chronic heart failure (CHF) with different response type on active orthostatic test (AOT).Material and methods. Totally 63 patients with CHF included with cardiomyopathy of ischemic and non-ischemic origin mostly of II-III functional class NYHA. All patients underwent echocardiography, heart rate variability analysis (HRV) resting and during DOT, plasma levels of NT-proBNP measured with C-reactive protein, tumor necrosis factor-α, interleukines (IL)-1β,6,10. According to the dynamics of HF% in AOT, all patients were divided into 2 groups: 1st group consisted of patients with decrease of HF% in AOT, 2nd group — with increase of HF% in AOT.Results. In patients from 2nd group we found larger heart chambers and volumes, as lower left ventricle ejection fraction comparing to the patients of the 1st group. Also in the 2nd group there were higher levels of NT-proBNP and IL-6. Resting patients of the both groups had very low values of all parameters of HRV. During AOT in the 1st group there was significant increase of HRV parameters, characterizing sympathetic and humoral systems activity. In the 2nd group the response on orthostasis was as a decrease of HRV values that characterize adreno-humoral influences, and sympathovagal index, characterizing sympathetic influence, was unchanged.Conclusion. Population of CHF patients is heterogenic according to neurohumoral activation. Decrease of sympatho-adrenal reactivity and relative increase of parasympathic influences in active orthostasis in CHF patients probably witnesses the exhaustion of sympatho-adrenal regulation and is a marker of CHF severity.